EFFECT OF AMINES AS PROTON VECTORS ON CATALYTIC HYDROGEN EVOLUTION REACTION ON COPPER - JAKAB, Ágnes; VASZILCSIN, Nicolae; MANEA, Florica; DAN, Mircea (Studia Universitatis Babeș-Bolyai Chemia, 2015)
In this study, the catalytic effect of several organic amines on hydrogen evolution reaction (HER) was studied on copper. Kinetic parameters of electrode process were determined from Tafel polarization curves to obtain more information about the catalytic effect of the organic amines. The best electrocatalytic effect was reached in 0.5 M H2SO4 solution for N,N-dimethylaniline (DMA). A correlation between molecular parameters and electrocatalytic effect of amines has been performed. A larger dipole moment determined for N,N-dimethylanilinium (DMAH+) showed that the orientation of these molecules are more favorable ordered on the electrode surface. Also, electrochemical impedance spectroscopy (EIS) technique was used to assess quantitatively the DMA effect over the electrochemical parameters for HER on copper. A significant enhancement of charge transfer rate was noticed with DMA concentration and temperature increasing. In addition, the adsorption behavior of DMA on copper surface followed the Langmuir adsorption isotherm. The low negative values of the standard Gibbs free energy of adsorption ΔGads at different temperature suggested a physical sorption. The value of the activation energy determined for 10-3 M DMA was 37% lower than that determined in its absence. A direct involvement of DMA in HER mechanism on the copper as proton carrier from bulk to the solution/metal interface was found.